Trabalho imaterial e valor-trabalho em Marx : uma análise sobre a valorização do capital - Cordeiro, Jadson (2014)
This dissertation is a critical overview of the theory developed by the authors: Antonio Negri, Michel Hardt and Maurizio Lazarato called \"theory of immaterial labor.\" This theory points to overcome the immediate work as a measure of capital appreciation, due to the rise of immaterial production today, considered the core element of production in general. The inability to measure an immaterial labor, because of abstract and subjective nature of production in these molds, make the thesis of Marx about surplus labor time as a source of value for analytical validity devoid of capital. In these terms, the work of a class is no longer a condition for the production of wealth from another class, thus exempting the conceptualization of classes as antagonistic social forces in the capitalist mode of production and founding a new social subject in the notion of General Intellect, modeled on the writings of Marx in the Grundrisse.